Performance analysis of simultaneous wireless information and power transfer relay network in railway Internet of things - Yaping LI; Ke XIONG; Yu ZHANG; Xi YANG (物联网学报, 2020)
The system performance of energy constrained dual-hop multi relay network was studied in railway Internet of things.The source node was deployed on the train to transmit energy and information to the relay node with constrained energy on the ground.The harvested energy was used by the relay node to forward information to the destination node,and the relay node used half-duplex amplify-and-forward mode.Considering that the relay circuit has energy activation threshold,the closed-form expression of outage probability and throughput in Rician fading channel was derived.The correctness of the theoretical analysis was verified by Monte Carlo simulation,and the effects of Rician factor,time switching factor,the number of source node antennas,total transmission power of source node,energy conversion efficiency,relative position of each node on the end-to-end outage probability and throughput were compared and analyzed under the two relay selection strategies with the shortest first hop distance and the shortest sum of dual-hop distance.When the train passes through each relay successively,the outage probability of the system decreases first and then in creases,and the throughput increases first and then decreases.The performance of the system with the shortest sum of dual-hop distances is better than that with the shortest first hop distance.